Munāsabah Ayat-Ayat Wasīlah dalam Tafsir Al-Mishbah: Konstruksi Makna dan Batas Teologis - Lembayung Aurandyta; Sulidar (CV Global Research Publication, 2026)
Studies of wasīlah have generally focused on theological debates, tawassul practices, and lexical interpretations, while the construction of its meaning through internal and thematic relationships among verses in Tafsir Al-Mishbah has not been systematically explained. This study aims to analyze the construction of meaning and the theological boundaries of wasīlah through the munāsabah of verses in Tafsir Al-Mishbah. This qualitative library research uses M. Quraish Shihab’s interpretations of Q.S. Al-Mā’idah [5]:34–36, Q.S. Al-Isrā’ [17]:57, Q.S. An-Nisā’ [4]:64, and Q.S. At-Taubah [9]:119 as its primary sources. Data were collected through documentation and examined using descriptive-interpretive content analysis by identifying, categorizing, and interpreting internal and thematic relationships among the verses. The findings demonstrate that the internal munāsabah of Q.S. Al-Mā’idah [5]:34–36 constructs wasīlah as a process of ethical transformation grounded in repentance, piety, and striving in the way of Allah. Its thematic relationships with other verses establish three dimensions of wasīlah: spiritual, ethical-practical, and social-prophetic. These dimensions encompass prayer, repentance, righteous deeds, obedience to the Prophet, acceptance of guidance, and companionship with righteous people. Tawḥīd constitutes its theological boundary: Allah is the ultimate purpose and the sole possessor of power, while any means of wasīlah possesses no independent power. This study formulates an integrative conceptual construction of wasīlah and provides a framework for evaluating tawassul practices according to their purposes, underlying beliefs, and conformity with the principle of tawḥīd.